Gender inequality on display in the flexibilisation of employment during the Covid-19 crisis in Slovenia - Štebe, Janez (Teorija in praksa, 2021)
Many risks are associated with the Covid-19 crisis and related lockdown measures in the areas of employment, the economy, and everyday life. Working parents have faced the challenge of combining their work and family obligations following the closure of schools and kindergartens. A considerable number have encountered a bigger risk of unemployment and the linked financial instability. The extensive literature analysing changes during Covid-19 suggests that women have tended to suffer more, been faced with both less stability since their employment statuses appear to be more precarious, and been disproportionally affected by the heavier burden of balancing family care and work obligations. Our own analysis of the most reliable survey data available shows corresponding changes in Slovenia, confirming that the crisis reveals certain less visible, already existing inequalities along with particular new gender inequalities, and in this respect also presents specific research design conditions for assessing otherwise hidden disparities. The results indicate the consequences for the subjective well-being of women compared to men of the more precarious employment and the stronger demand for family care.
Keywords: Covid-19; Delo in družina; Delo na domu; Employment; Epidemics; Epidemije; fleksibilnost zaposlitve; Gender inequality; Home labor; Spolna neenakost; Work and family; zadovoljstvo z življenjem; Zaposlitev